2021
DOI: 10.1103/physrevb.104.045141
|View full text |Cite
|
Sign up to set email alerts
|

Electron self-energy from quantum charge fluctuations in the layered tJ model with long-range Coulomb interaction

Abstract: Employing a large-N scheme of the layered t-J model with the long-range Coulomb interaction, which captures the fine details of the charge excitation spectra recently observed in cuprate superconductors, we explore the role of charge fluctuations on the electron self-energy. We fix the temperature at zero and focus on quantum charge fluctuations. We find a pronounced asymmetry of the imaginary part of the self-energy Im (k, ω) with respect to ω = 0, which is driven by strong electron correlation effects. The q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
(318 reference statements)
0
1
0
Order By: Relevance
“…Although the medium energy resolution of those measurements (ΔE ≈ 0.8 eV) precluded a more precise determination of their energy profile, the results suggested that these quasi-circular dynamic correlations (QCDCs) appear broad over the mid-infrared ranges (defined approximately as 100 to 900 meV). This scattering manifold, which may result from combined short-and long-range Coulomb interactions (15)(16)(17), would provide a large variety of wave vectors for connecting all points of the Fermi surface (i.e., an effective isotropic scattering). However, it is not yet experimentally known whether this manifold extends to electron scattering at lower energies, in the quasi-elastic regime.…”
Section: Introductionmentioning
confidence: 99%
“…Although the medium energy resolution of those measurements (ΔE ≈ 0.8 eV) precluded a more precise determination of their energy profile, the results suggested that these quasi-circular dynamic correlations (QCDCs) appear broad over the mid-infrared ranges (defined approximately as 100 to 900 meV). This scattering manifold, which may result from combined short-and long-range Coulomb interactions (15)(16)(17), would provide a large variety of wave vectors for connecting all points of the Fermi surface (i.e., an effective isotropic scattering). However, it is not yet experimentally known whether this manifold extends to electron scattering at lower energies, in the quasi-elastic regime.…”
Section: Introductionmentioning
confidence: 99%